2021
DOI: 10.3390/jcm10122696
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Viable SARS-CoV-2 Virus from Feces of an Immunocompromised Patient Suggesting a Possible Fecal Mode of Transmission

Abstract: (1) Background: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) excretion in stools is well documented by RT-PCR, but evidences that stools contain infectious particles are scarce. (2) Methods: After observing a Corona Virus 2019 Disease (COVID-19) epidemic cluster associated with a ruptured sewage pipe, we search for such a viable SARS-CoV-2 particle in stool by inoculating 106 samples from 46 patients. (3) Results: We successfully obtained two isolates from a unique patient with kidney transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 25 publications
1
40
0
3
Order By: Relevance
“…Respiratory droplets and aerosols may contain high titers of viral particles [ 38 , 39 , 40 ] and SARS-CoV-2 infectivity is retained for over 3 h in experimentally produced aerosols [ 41 ]. On the contrary, occurrence of infectious virus in feces and urine has been questioned: detection of SARS-CoV-2 in human feces (reviewed in Foladori et al 2020 [ 42 ]) is indeed a common feature in infected subjects, but isolation of infectious virus from this clinical specimen has been achieved in a limited number of cases [ 43 , 44 , 45 , 46 ], while other studies failed to do so [ 47 , 48 , 49 ]. Therefore, it may be hypothesized that feces and urine probably contain either low levels or no infectious SARS-CoV-2 particles and that, based on low predicted abundances and limited environmental survival, the likelihood of SARS-CoV-2 transmission though sewage-contaminated water or bivalve shellfish is extremely low or negligible [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory droplets and aerosols may contain high titers of viral particles [ 38 , 39 , 40 ] and SARS-CoV-2 infectivity is retained for over 3 h in experimentally produced aerosols [ 41 ]. On the contrary, occurrence of infectious virus in feces and urine has been questioned: detection of SARS-CoV-2 in human feces (reviewed in Foladori et al 2020 [ 42 ]) is indeed a common feature in infected subjects, but isolation of infectious virus from this clinical specimen has been achieved in a limited number of cases [ 43 , 44 , 45 , 46 ], while other studies failed to do so [ 47 , 48 , 49 ]. Therefore, it may be hypothesized that feces and urine probably contain either low levels or no infectious SARS-CoV-2 particles and that, based on low predicted abundances and limited environmental survival, the likelihood of SARS-CoV-2 transmission though sewage-contaminated water or bivalve shellfish is extremely low or negligible [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible variations on these routes include direct contact from an infected person who has contaminated their fingers from their own nose or mouth. Although faecal, urinary, and sexual transmission are theoretically possible,2728293031 none has been confirmed in humans.…”
Section: Evidence On Transmission Routesmentioning
confidence: 99%
“…Wastewater-based epidemiology (WBE) is a tool to monitor the presence/circulation of biological or chemical agents in a population [40,41]. The detection of SARS-CoV-2 in the urine and feces of patients with symptomatic and asymptomatic infection [42,43] implies that the virus may be detected in the wastewater [44][45][46]. Several studies have shown that SARS-CoV-2 RNA dynamics in raw wastewater coincide with the dynamics of COVID-19 cases [45,47].…”
Section: Sars-cov-2 In Wastewatermentioning
confidence: 99%